New national and state records of Neotropical Staphylinidae (Insecta: Coleoptera) - Asiain, Julieta; Márquez, Juan; Irmler, Urlich (Zootaxa, 2015)
Eighteen new national records of nine species of Osoriinae (Staphylinidae) are added for 10 Neotropical countries. Additionally, 17 species of three subfamilies are first recorded from ten States of México. The distributional patterns of the studied species are commented and the congruence with species of different families of Coleoptera and Odonata previously analyzed is discussed. Finally, we conclude that some of these patterns can be proposed as hypothesis of primary biogeographic homology.